БНСУ-ЫН ТӨРИЙН БУС БАЙГУУЛЛАГА БОЛОН МОНГОЛЫН ТӨРИЙН БУС БАЙГУУЛЛАГУУДЫН ХАМТЫН АЖИЛЛАГАА - Лий Дэ Хаг (Politology, 2023)
The yellow sand problem that is from desertization is the problems of northeast Asia and whole world. Mongolia is the country that fastly desertizing and being a root of the yellowsand. Currently, there are many anti desertizing movements like planting the trees; however, it could not show explicit result yet. To make these movements to result much more, not only the government, but also Mongolian citizen and non - government organizations (NGO) should participate together. Moreover, when Korean NGOs help and coopereate together with Mongolian NGOs, anti desertization can be more activated.